Nightmare frequency and feminine and masculine sex roles: An online survey - Schredl, Michael; Göritz, Anja (Dreaming, 2021)
Previous research has documented a gender difference in nightmare frequency, with women reporting nightmares more often than men. Several explanations have been suggested but empirical research in this area is scarce. The present online survey was completed by 1,808 participants (1,110 women, 698 men) with a mean age 45.64 ± 15.33 years. The gender effect was no longer significant if masculinity/femininity, both showing negative or positive correlations to nightmare frequency, respectively, were statistically controlled. This finding indicates that gender roles may at least partially explain the gender difference in nightmare frequency. The data regarding the self-rated femininity suggest that having nightmares might be attributed to a feminine sex role. It would be interesting to study whether or not such attributions are linked to the fact that nightmare sufferers rarely seek professional help for their condition. (PsycInfo Database Record (c) 2021 APA, all rights reserved)